Synthesis and coloration of highly dispersed NiTiO3@TiO2 yellow pigments with core-shell structure. Issue 8 (July 2017) - He, Xuanmeng; Wang, Fen; Liu, Hui; Li, Junqi; Niu, Lijun
Abstract: The highly dispersed NiTiO3 @TiO2 yellow pigments with core-shell structure were prepared through calcinations of precursors obtained from the precipitation of Ni 2+ on the surface of TiO2 particles. The synthesized pigments were characterized by XRD, SEM, TEM, Uv–vis spectroscopy and colorimetry. The pigments were found to consist of TiO2 core and outer ilmenite NiTiO3 shell. The optical absorption of Ni 2+ in octahedral coordination produced intense yellow colors. Compared with pure NiTiO3, the NiTiO3 @TiO2 pigments presented higher yellow and lower red hues, resulted in intense yellow colors. The particle size distribution of the prepared pigments and ζ potential measurement indicated that the NiTiO3 -0.75@TiO2 pigments were uniform and well-dispersed in glycol solvents, and they form relatively more stable suspension than pure NiTiO3 pigments. Meanwhile, these pigments were stable in commercial low–temperature ceramic glazes, possessed more brilliant yellowish colors than pure NiTiO3 prepared by sol-gel method.